The assassination of Abraham Lincoln - Marinelli, Deborah A. (New York : Rosen Pub. Group, 2002)
Discusses the lives of Abraham Lincoln and John Wilkes Booth, the political reasons for, and details of, the assassination plan, and Lincoln's legacy.
The night Lincoln was shot -- The climate surrounding the assassination -- John Wilkes Booth and the unfolding of the assassination -- The reaction to President Lincoln's assassination -- How Lincoln's assassination changed the course of history.
Includes bibliographical references (p. 61) and index.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Assassination -- Juvenile literature; Lincoln, Abraham, -- 1809-1865 -- Assassination; Booth, John Wilkes, -- 1838-1865.; Assassins; United States -- History -- Civil War, 1861-1865.